Most anti-BrdU antibodies react with 2'-deoxy-5-ethynyluridine -- the method for the effective suppression of this cross-reactivity - Liboska, Radek; Ligasová, Anna; Strunin, Dmytro; Rosenberg, Ivan; Koberna, Karel (PloS one, 2012)
5-Bromo-2'-deoxyuridine (BrdU) and 2'-deoxy-5-ethynyluridine (EdU) are widely used as markers of replicated DNA. While BrdU is detected using antibodies, the click reaction typically with fluorescent azido-dyes is used for EdU localisation. We have performed an analysis of ten samples of antibodies against BrdU with respect to their reactivity with EdU. Except for one sample all the others evinced reactivity with EdU. A high level of EdU persists in nuclear DNA even after the reaction of EdU with fluorescent azido-dyes if the common concentration of dye is used. Although a ten-time increase of azido-dye concentration resulted in a decrease of the signal provided by anti-BrdU antibodies, it also resulted in a substantial increase of the non-specific signal. We have shown that this unwanted reactivity is effectively suppressed by non-fluorescent azido molecules. In this respect, we have tested two protocols of the simultaneous localisation of incorporated BrdU and EdU. They differ in the mechanism of the revelation of incorporated BrdU for the reaction with antibodies. The first one was based on the use of hydrochloric acid, the second one on the incubation of samples with copper(I) ions. The use of hydrochloric acid resulted in a significant increase of the non-specific signal. In the case of the second method, no such effect was observed.
Keywords: Cross Reactions; biotinylace; protilátky; Fluorescent Dyes; Biotinylation; zkřížené reakce; Deoxyuridine; fluorescenční mikroskopie; Bromodeoxyuridine; bromodeoxyuridin; Antibody Affinity; HeLa buňky; biologický transport; Antibodies; lidé; Microscopy, Fluorescence; HeLa Cells; Humans; barvení a značení; afinita protilátek; fluorescenční barviva; DNA; Staining and Labeling; deoxyuridin; Biological Transport